The Role Of Instagram As A Promotional Media In Increasing The Number Of Visitors - Dharta, Firdaus Yuni; Firdaus, Adhy; Pranawukir, Iswahyu; Angellia, Filda; Hamboer, Maria Jashinta Elisabet (International Journal of Artificial Intelligence Research, 2023)
This study aims to investigate the use of Instagram as a promotional medium. A qualitative research methodology with a case study approach was adopted, and Cafe XYZ in Jakarta was chosen as the research object. The findings shed light on the effectiveness of using Instagram for marketing purposes. Data collection comprised interviews, observation, and documentation from a range of participants, including owners, customers, employees, and followers of Cafe XYZ. The analysis investigated the factors that motivate Cafe to promote its products on Instagram. Utilizing customer reviews and advertising menus for sale are key strategies. The effectiveness of Instagram for promotion stems from its universal social media usage across all age groups. Additionally, its advanced features allow users to easily search for locations and explore products via hashtags (#).